IMPLEMENTATION OF THE RIGHT TO OBTAIN LEGAL ASSISTANCE FOR POOR CITIZENS AT THE INVESTIGATION STAGE - Oktri Sasmita Yudha (Universitas Lampung, 2023)
Legal Aid is a right owned by a suspect/defendant to assist the suspect/defendant at various stages of the ongoing trial process. Investigators at this stage of the investigation process are required to give suspects the right to be accompanied by legal advisers regardless of the economic status of the suspect so that during the investigation process, the suspect becomes a subject and not an object and is treated equally before the law without discriminating between economic status. The problem in this article is implementing the right to legal Aid for the poor at the investigation stage and what funds are the inhibiting factors in implementing the right to legal Aid for the poor at the investigation stage. The method used in this study uses an empirical normative method with a statute approach. The results and discussion in this study indicate that several efforts are needed to increase effectiveness, including throwing the quality of advocate human resources, signing a joint commitment/agreement between law enforcement officials regarding the implementation of the provision of legal Aid, giving strict rewards and punishments to Legal Aid Organizations.